EXPLORING ERRORS ON THE BASIC ENGLISH TRANSLATION TO THE SECOND SEMESTER STUDENTS OF ECONOMY EDUCATION STUDY PROGRAM UNIVERSITAS PGRI RONGGOLAWE TUBAN - Budi Susatyo (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2017)
This paper presents a review of research that investigates the problem and analyzes errors of basic translation in English to the students of the Economic and Accounting Education Study Program of PGRI Ronggolawe University (UNIROW) Tuban. The purpose of this study is to identify factors for achieving the most basic level of English Translation. The main focus of this study is to examine why students appear to be unable to achieve basic level English translation even after more than 8 years of learning English (after learning English from elementary, junior and senior high school.) The purpose of the study is to describe the mistakes in the translation of the basic of the Indonesian language into English by giving a test on the students of the study program.